Computational Fluid Dynamics (CFD) of Chemical Processes - Lim, Young-Il (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
In this Special Issue, one review paper highlights the necessity of multiscale CFD, coupling micro- and macro-scales, for exchanging information at the interface of the two scales. Four research papers investigate the hydrodynamics, heat transfer, and chemical reactions of various processes using Eulerian CFD modeling. CFD models are attractive for industrial applications. However, substantial efforts in physical modeling and numerical implementation are still required before their widespread implementation.